2014
DOI: 10.1002/2013gb004754
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐sea coral record of human impact on watershed quality in the Mississippi River Basin

Abstract: One of the greatest drivers of historical nutrient and sediment transport into the Gulf of Mexico is the unprecedented scale and intensity of land use change in the Mississippi River Basin. These landscape changes are linked to enhanced fluxes of carbon and nitrogen pollution from the Mississippi River, and persistent eutrophication and hypoxia in the northern Gulf of Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that high δ 15 N values are associated with the river water itself, particulate organic matter, entrained plankton, and shrimp associated with the plume (Wissel and Fry 2005;Dorado et al 2012). Additionally, increases in deepwater coral δ 15 N values have been attributed to increased nutrient loading of river waters, demonstrating both the extent of river influence and its effect on N isotopic compositions (Williams et al 2007;Prouty et al 2014). If this enriched N source was incorporated into the local food web at East Cameron, then consumers such as Red Snapper would be expected to show higher δ 15 N values relative to individuals from areas with a lesser riverine influence, which was observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that high δ 15 N values are associated with the river water itself, particulate organic matter, entrained plankton, and shrimp associated with the plume (Wissel and Fry 2005;Dorado et al 2012). Additionally, increases in deepwater coral δ 15 N values have been attributed to increased nutrient loading of river waters, demonstrating both the extent of river influence and its effect on N isotopic compositions (Williams et al 2007;Prouty et al 2014). If this enriched N source was incorporated into the local food web at East Cameron, then consumers such as Red Snapper would be expected to show higher δ 15 N values relative to individuals from areas with a lesser riverine influence, which was observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Macroalgae are known to accumulate Re and Os from seawater (Mas et al, ; Prouty et al, ; Racionero‐Gómez et al, ; Racionero‐Gómez et al, ; Rooney et al, ; Scadden, ; Yang, ), and recent studies have shown that macroalgae can act as a proxy for the 187 Os/ 188 Os of the seawater in which it lived (Racionero‐Gómez et al, ) and has been utilized to trace coastal inputs (Rooney et al, ). In addition, the 187 Re/ 188 Os of macroalgae has provided important insights into the incorporation of Re and Os into organic matter and sedimentary material (Racionero‐Gómez et al, ; Racionero‐Gómez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 187 Re/ 188 Os of macroalgae has provided important insights into the incorporation of Re and Os into organic matter and sedimentary material (Racionero‐Gómez et al, ; Racionero‐Gómez et al, ). However, the sources from which Re and Os are taken up, the influence of tidal mixing on the 187 Os/ 188 Os and 187 Re/ 188 Os of macroalgae and the cause of exceptionally high Re abundance and thus extremely high 187 Re/ 188 Os compositions in macroalgae are not fully understood (Mas et al, ; Prouty et al, ; Racionero‐Gómez et al, ; Racionero‐Gómez et al, ; Rooney et al, ; Scadden, ; Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…This trophic position calculated for the Muricella coral was higher than that calculated for deep‐sea black corals from the Gulf of Mexico at 300‐m depth of ∼2 determined using Glu‐Phe Eq. (Prouty et al ) but less than that reported for the gold coral Kulamanamana haumeaae specimens from the Island of O'ahu in the Hawaiian Islands at 450‐m depth with an averaged calculated trophic position of 3.0 using Glu‐Phe Eq. and .7 using Eq.…”
Section: Discussionmentioning
confidence: 88%
“…In the Hawaiian K. haumeaae coral and the NW Atlantic P. resedaeformis coral, δ 15 N gly is elevated relative to δ 15 N Phe yet still follows the same trend trends over the lifespan of the corals analyzed (Sherwood et al ). In contrast in the deep‐sea black corals, δ 15 N Phe and δ 15 N gly are the same (Prouty et al ). Thus, the enrichment of δ 15 N gly relative to δ 15 N Phe may reflect either regional nitrogen dynamics or coral‐taxa variability.…”
Section: Discussionmentioning
confidence: 99%